Mathematikbezogene affektive Schülermerkmale fördern: Eine explorative Untersuchung zum Potential von Fermi-Aufgaben (mathematica didactica, 2020)
Mathematics-related affect such as anxiety, self-efficacy and interest can influence the learning of mathematics. Based on prototypical processes of the modelling cycle, we argue that Fermi problems in particular can have the potential to influence these student characteristics positively and thus can be implemented into mathematics classrooms to support students with respect to multi-dimensional educational goals. We also report on an exploratory study. The results stemming from 30 students in two tenth grades of a vocational high school are in line with our assumption.